THE ANALYSIS OF THEORY OF PLANNED BEHAVIOR AND RELIGIOSITY FACTORS ON WILLINGNESS TO PAY WAQF OF MUHAMMADIYAH COMMITTEE IN SURABAYA - Mutia Fatiha Pratama; Raditya Sukmana (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study is aimed at analyzing the effect simultaneously and partially on Attitude, Subjective Norms, Behavior Control and Religiosity factors on willingness to do waqf on Muhammadiyah Committee in Surabaya. The research method in selecting respondents was determined intentionally (purposive sampling), namely as many as 50 PCM committees (Muhammadiyah Branch Manager) at the District level in the city of Surabaya. This study uses multiple linear regression analysis with the dependent factor Willingness (Y) Affected by Independent Factors including Attitude X1, Subjective Norms X2, Behavior Control X3 and Religiosity X4. The results obtained in this study are Attitude, Subjective Norms, Behavior Control variables have a significant effect on Willingness to do waqf variables. In contrast, the Religiosity variable does not have a significant effect on the Willingness variable in representation.Keywords: Attitude, Subjective Norms, Behavior Control, Religiosity, Willingness to do WaqfREFFERENCE Ajzen, Icek. (1991). Theory of planned Behavior. Organizational Behavior and Human Decision Process, Vol. 50, 179-211.Ajzen, Icek. (2005). Attitude, personality, and behavior, second edition. USA: Open University press.Islam, J. U., & Rahman, Z. (2017). Awareness and willingness towards Islamic banking among Muslims: An Indian perspective. International Journal of Islamic and Middle Eastern Finance and Management, 10(1), 92-101.Jogiyanto. (2007). Sistem informasi keperilakuan. Yogyakarta: AndiOsman, A. F., Mohammed, M. O., & Fadzil, A. (2016). Factor influencing cash Waqf giving behavior: A revised theory of planned behavior. Journal of Global Business and Social Entrepreneurship, 1(2), 12-25.P Kotler, G Amstrong. (2001). Prinsip-prinsip pemasaran, jilid 2, edisi ke-8. Jakarta: Penerbit Erlangga.Rita L. Atkinson dan Richard C. Atkinson. (1983). Pengantar psikologi 1, jilid 1. Jakarta: Erlangga.Rizal, H., & Amin, H. (2017). Perceived ihsan, Islamic egalitarianism and Islamic religiosity towards charitable giving of cash waqf. Journal of Islamic Marketing, 8(4), 669-685.Santoso, Singgih. (2010). Statistik parametrik, konsep dan aplikasi dengan SPSS, cetakan Pertama. Jakarta: PT Elex Media Komputindo.Santoso, Singgih. (2012). Panduan lengkap SPSS Versi 20. Jakarta: PT Elex Media Komputindo.Sekaran, U., (2006). Metodologi penelitian untuk bisnis, edisi 4. Jakarta: Salemba Empat.Setiawan dan Dwi Endah Kusrini. (2010). Ekonometrika. Yogyakarta: Andi.Siregar, Syofian. (2015). Metode penelitian kuantitatif dilengkapi dengan perbandingan perhitungan manual & SPSS. Jakarta: Prenadamedia Group.SK, Lubis. (2010). Wakaf dan pemberdayaan umat. Jakarta: Sinar Grafika.Sugiyono dan Agus Susanto. (2015). Cara mudah belajar SPSS dan Lisrel. Teori dan Aplikasi untuk Analisis Data Penelitian. Bandung: CV. Alfabeta.Sugiyono, M. P. K. (2013). Kualitatif, dan kombinasi (mixed methods). Bandung: Alfabeta.Tanjung, H., & Devi, A. (2013). Metodologi penelitian ekonomi Islam. Jakarta: Gramata Publishing.